Data backup security in cloud storage system - Атаян, Борис Геннадьевич; Багдасарян, Татевик Араевна (Ukrainian Scientific Journal of Information Security, 2016)
Cloud backup system is proposed, which provides means for effective creation, secure storage and restore of backups in Cloud. For data archiving new efficient SGBP file format is being used in the system, which is based on DEFLATE compression algorithm. Proposed format provides means for fast archive creation, which can contain significant amounts of data. Modern approaches of backup archive protection are described in the paper. Also the SGBP format is compared to heavily used ZIP format (both ZIP32 and ZIP64). SGBP backup archives are protected using symmetric encryption AES algorithm. Because in case of loss, distortion or leak of the encryption key backup archive will become inaccessible, there is no doubt that the SGBP encryption keys need special protection and management. The cryptographic keys of SGBP backups are protected using distributed cloud storage system, which is based on Shamir’s threshold secret sharing scheme. After secret sharing all individual secret shares are distributed and saved to different cloud storage services (e.g. Dropbox, GoogleDrive, SkyDrive etc.). Modules for key share validity check and share update without key reconstruction are included in the system.